The Impact Of Metformin, Magnesium, And Vitamin - D On Mitigating Lipid Metabolism In Streptozotocin (Stz)-Induced Diabetes In An Albino Rat Model - Sukanya T Chintha Madhusudan; Kishore Salikineedy (Journal of Advanced Zoology, 2024)
This research investigates the impact of metformin, magnesium, and vitamin D on lipid metabolism in streptozotocin-induced diabetes using an albino rat model. Metformin, known for its glucose-lowering effects, is explored for potential influences on lipid metabolism, while magnesium and vitamin D, essential nutrients, are examined for their roles in modulating lipid abnormalities in diabetes. The study, employing six groups of male Wistar rats with distinct interventions, including metformin alone and in combination with vitamin D and/or magnesium, aims to unveil synergistic or additive effects on lipid regulation. Ethical approval was obtained, and diabetes induction, treatment administration, euthanasia, and lipid profile estimation were conducted following established protocols. Untreated diabetic rats exhibited significant lipid parameter deviations compared to the control group. Metformin alone demonstrated positive effects, further enhanced by combinations with vitamin D and/or magnesium. The metformin + vitamin D + magnesium combination yielded the most favorable outcomes in liver and kidney lipid profiles, suggesting a potential synergistic effect in mitigating diabetes-induced lipid changes. The study emphasizes the importance of multifaceted approaches for managing diabetes-associated complications. Validation of these findings and assessing translational potential in human diabetes management warrant further research and clinical studies.